Without an equality sign the given expression can't be considered to be an equation and so therefore it has no solutions.
Chat with our AI personalities
5=3x+2 3x+2-2=5-2 3x=3 ------ 3 x=1
I understand the equation to be y = -3x - 2 and the point to be (5,1). I substitute 1 for each appearance of y and 5 for each appearance of x: 1 = -3(5) - 2 = -15 - 2 = -17, which is not a true statement. Therefore, that is not a solution. To get a solution, set x=1, and calculate y by substituting this value (1) for x wherever it appears: y = -3(1) - 2 = -3 - 2 = -5. Therefore, (-5,1) is a solution. (I suspect that this is what you meant to put in the question.)
(x + 1)(3x + 10)
3x**2+x-10 Multiply first and last terms 3*-10=-30 Find factors of -30 that add up to second term 6+-5=1 rewrite 3x**2-5x+6x-10 Factor pairs of terms 3x**2-5x+6x-10 = x(3x-5)+2(3x-5) Factor x(3x-5)+2(x-5) = (x+2)(3x-5)
its a beautiful thang baby luk at my chain vbs carrots make me check out my ice